2011
DOI: 10.1073/pnas.1016569108
|View full text |Cite
|
Sign up to set email alerts
|

Anti–ErbB-2 mAb therapy requires type I and II interferons and synergizes with anti–PD-1 or anti-CD137 mAb therapy

Abstract: Trastuzumab, a monoclonal antibody targeting human epidermal growth factor receptor-2 (HER2/ErbB-2), has become the mainstay of treatment for HER2-positive breast cancer. Nevertheless, its exact mechanism of action has not been fully elucidated. Although several studies suggest that Fc receptor-expressing immune cells are involved in trastuzumab therapy, the relative contribution of lymphocyte-mediated cellular cytotoxicity and antitumor cytokines remains unknown. We report here that anti-ErbB-2 mAb therapy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
332
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 427 publications
(361 citation statements)
references
References 32 publications
14
332
2
1
Order By: Relevance
“…Further studies are necessary to identify the site of suppression in our model. PD-1-blocking antibodies are being discussed for clinical application in cancer (43), persistent viral hepatitis (44), and AIDS (45) as a means to invigorate suppressed or exhausted T-cell responses. Also antibody responses were found to be increased after PD-1 blockade, which our results suggest to be due to inhibition of T reg function.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are necessary to identify the site of suppression in our model. PD-1-blocking antibodies are being discussed for clinical application in cancer (43), persistent viral hepatitis (44), and AIDS (45) as a means to invigorate suppressed or exhausted T-cell responses. Also antibody responses were found to be increased after PD-1 blockade, which our results suggest to be due to inhibition of T reg function.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-PD-1 antibody therapy has been shown to enhance the response to radiotherapy and DC vaccines in established breast cancers (Verbrugge et al, 2012;Ge et al, 2013). Anti-PD-1 antibody also significantly improves the effectiveness of the anti-HER2 monoclonal antibody in immunocompetent mice (Stagg et al, 2011). Together, these studies suggest that anti-PD-1 may be used in combination with other therapies to improve the overall treatment efficacy in breast cancer.…”
Section: Immune Checkpoint Blockadementioning
confidence: 75%
“…23 Recently, it was reported that the therapeutic effect of anti-HER2/neu did not require CD4 1 T cells, but did depend on both type I and type II interferon. 24 In other models of oncogenic blockade, however, it was reported that tumor regression did require CD4 1 T cells. 25 Thus, the detailed mechanism of CD4 1 T-cell activation and the role of these cells in antibody-mediated tumor regression are unclear.…”
Section: Antibody Therapymentioning
confidence: 99%